Magnetic and magnetocaloric properties of the Co2-xMnxB system by experiment and density functional theory. (15th February 2019) - Ener, Semih; Fries, Maximilian; Hammerath, Franziska; Opahle, Ingo; Simon, Eszter; Fritsch, Patrizia; Wurmehl, Sabine; Zhang, Hongbin; Gutfleisch, Oliver
Abstract: The Co2 B system shows a significant magnetovolume effect around its Curie temperature which makes it potentially attractive for magnetocaloric applications or thermomagnetic power generation, as a large coupling between the lattice and spin degrees of freedom is expected. We report on the synthesis of a series of Co2-x Mn x B alloys and the investigation of their properties. The structural analysis indicates a single phase behavior up to x = 0.8 with no structural symmetry changes throughout the series. Measurements of both, macroscopic and local magnetic properties, reveal an anomalous behavior of the spontaneous magnetization, Curie temperature, and element-specific magnetic moments as a function of manganese concentration. The elemental contributions to the magnetization are analyzed using nuclear magnetic resonance (NMR) studies. Density functional theory (DFT) calculations guide us in the understanding of the origin of the observed anomaly, which is due to a complex magnetic coupling behavior between Mn atoms, which significantly affects the corresponding exchange interactions. The magnetocaloric properties of the Co2-x Mn x B alloys show that the maximum entropy change peak temperature can be shifted between room temperature and 450 K upon variation of the manganese concentration without significant impact on the magnetocaloric response. The highest entropy change of −1.37 J k g − 1 K − 1 at 442 K is obtained for x = 0.1 for a field change of 2 T. This value is, however, quite low for any possible magnetocaloric or thermomagnetic power generation applications. Nevertheless, the good agreement between the advanced characterization and theory gives a deeper understanding of the Co2-x Mn x B material system which can in the future be extended to other systems. Graphical abstract: Image 1